Digital Transformation and Value Chain Efficiency in Agricultural Marketing - A. St. Fatmawaty; Silvans Tande Bura (CV. HEI PUBLISHING INDONESIA, 2025)
This study empirically analyzed the impact of Digital Transformation (DT) on Agricultural Marketing Value Chain Efficiency (VCE) across 12 developing economies from 2019 to 2023, utilizing a Fixed Effects (FE) panel data model. The research specifically quantified the contribution of Digital Access (ACCESS), ICT Infrastructure (INFRA), and Digital Policy (POLICY) on Marketing Margin (MM), Post-Harvest Loss (PHL), and Farmers’ Terms of Trade (FTT). The FE results indicate that ACCESS and INFRA robustly and significantly reduce MM and PHL while positively impacting FTT. Notably, INFRA showed the largest effect: a 1 unit increase in INFRA (mobile-broadband subscriptions per 100 inhabitants) correlates with a 0.398 percentage point drop in MM, confirming that network quality is paramount for supply chain streamlining and reducing information asymmetry. Conversely, the POLICY variable was largely insignificant. Supplementary analysis attributes this weakness to policy frameworks overemphasizing upstream (production) technology and neglecting critical downstream (marketing and logistics) inefficiencies. The study concludes that while market-driven DT investment is a proven driver of VCE, the full potential of government intervention requires a strategic reorientation toward addressing downstream value chain challenges.